Rebel without a cause - Stern, Stewart; Weisbart, David; Ray, Nicholas, 1911-; Rosenman, Leonard; Dean, James, 1931-1955.; Wood, Natalie; Mineo, Sal.; Doran, Ann.; Allen, Corey; Hopper, Dennis, 1936-; Shulman, Irving; Warner Bros. Pictures; et al. (Burbank, CA : Warner Home Video, 1999)
The teen-aged son of a well-to-do family gets involved in violence when he attempts to win the approval of a gang of high-school hoodlums.
"Adaption by Irving Schulman from story by Nicholas Ray."
Originally released as motion picture in 1955.
Special features: Rediscovering a rebel; 3 Behind the cameras segments from the Warner Bros. presents TV series, including a "safe-driving" interview withdrawn from airing following Dean's death (interviews with Natalie Wood, Jim Backus, and James Dean); 3 theatrical trailers; interactive menus; production notes; scene access.
Director of photography, Ernest Haller; film editor, William Ziegler ; music, Leonard Rosenman.
James Dean, Natalie Wood, Sal Mineo, Jim Backus, Ann Doran, Corey Allen, Dennis Hopper.
Not rated.
Keywords: Juvenile delinquents -- United States -- Drama; Youth -- United States -- Conduct of life -- Drama; Feature films; Films for the hearing impaired; United States -- Drama